ChemInform Abstract: Multicomponent Green Synthesis, Spectroscopic and Structural Investigation of Multi‐Substituted Imidazoles. Part 1. Issue 14 (March 2016) - Mohamed, Shaaban K.; Simpson, Jim; Marzouk, Adel A.; Talybov, Avtandil H.; Abdelhamid, Antar A.; Abdullayev, Yusif A.; Abbasov, Vagif M.
Abstract: Tetra‐substituted imidazole derivatives are obtained under solvent‐free and green reaction conditions by four‐component cyclocondensation of benzene, ethanolamine, various aromatic aldehydes, and ammonium acetate using the novel, reusable ionic liquid catalyst, diethylammonium hydrogen sulfate.